A colour-sequence enhanced particle streak velocimetry method for air flow measurement in a ventilated space. (1st February 2017) - Wang, Huan; Li, Xianting; Shao, Xiaoliang; Wang, Baolong; Lin, Yanqing
Abstract: Airflow measurement is crucially important for studying the indoor environment. Two primary approaches that use bubbles as seeds to visualize and track the air flow are Particle Tracking Velocimetry (PTV) and Particle Streak Velocimetry (PSV). After analysing their advantages and drawbacks, this paper introduces a new approach: Colour Sequence enhanced Particle Streak Velocimetry (CSPSV). The core component of CSPSV is the newly designed Colour Sequence Illumination System (CSIS), which consists of three types of controlled flash lights of different colours and one type of white light. By changing the illumination colour of the test zone in a given sequence, the time sequence information is added onto a single image, which enables easier execution of the algorithm for three-dimensional (3D) reconstruction and streak pair matching. A CSPSV prototype was developed by marking the time sequence information with coloured light, and the accuracy of the CSPSV prototype was verified by comparing the movement of white dots on a rotating board. The weak jet and thermal plumes were also measured to demonstrate the reliability of the CSPSV method. It is observed that the relative magnitude error is below 5%, and CSPSV combines the advantages of PTV and PSV, which reduces the requirement for high-speed cameras. In addition, the new approach can be easily extended and used to measure the air flow in a large space. Highlights: Colour sequence illumination system is developed to mark time sequence of bubbles. A prototype of colour sequence enhanced particle streak velocimetry was built. Relative error of CSPSV is blow 5% for normal speed in ventilated space. CSPSV is more effective in streak matching and high speed 3D path tracking.